2001
DOI: 10.1128/jvi.75.23.11496-11502.2001
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Attenuation of Rabies Virus by Simultaneously Modifying the Dynein Light Chain Binding Site in the P Protein and Replacing Arg333 in the G Protein

Abstract: Rabies virus (RV) is a highly neurotropic virus that migrates from the portal of entry to the central nervous system (CNS). The cytoplasmic dynein light chain (LC8), which is involved in a variety of intracellular motile events, was shown to interact with RV phosphoprotein (P). In order to determine the functional significance of this interaction, P residues 143 to 149 or 139 to 149 encompassing a conserved LC8-interacting motif (K/RXTQT) were deleted from recombinant viruses SAD-L16 and SAD-D29. These viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
12

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 34 publications
5
82
0
12
Order By: Relevance
“…In contrast, Mebatsion (27) had previously demonstrated that deletion of the dynein LC8-BD did not affect viral replication in nonneuronal BHK-1 cells. However, when murine neuroblastoma (NA) cells were infected synchronously at a multiplicity of infection (MOI) of 10, r⌬LC8-N2c grew to 5-to 10-fold lower titers than rN2c (SI Fig.…”
Section: Deletion Of the Lc8-bd Attenuates Growth On Neuronal Cell LImentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Mebatsion (27) had previously demonstrated that deletion of the dynein LC8-BD did not affect viral replication in nonneuronal BHK-1 cells. However, when murine neuroblastoma (NA) cells were infected synchronously at a multiplicity of infection (MOI) of 10, r⌬LC8-N2c grew to 5-to 10-fold lower titers than rN2c (SI Fig.…”
Section: Deletion Of the Lc8-bd Attenuates Growth On Neuronal Cell LImentioning
confidence: 99%
“…In fact, LC8 is incorporated into mature RV virions (26), providing additional evidence that LC8 might be involved in the attachment of the viral particle to the dynein motor complex on entry into the host cell. However, subsequent experiments in 7-day-old mice demonstrated that removing the LC8-BD simply delayed onset of disease, still allowing the transport of RV into the CNS (27,28).…”
Section: Construction Of Recombinant Rvsmentioning
confidence: 99%
“…However, mutant viruses with deletion in phosphoprotein encompassing LC8-interacting motif retained their neuroivasiveness and virulence [72]. Neuroattenuation required simultaneous substitution of arginine at position 333 of viral glycoprotein with deletion of LC8, reinforcing that rabies viral glycoprotein plays a more important role than phosphoprotein [72]. Several viruses such as HIV, poliovirus, herpes simplex virus, African swine flu, and adenovirus use dynein for intracellular transport of the virus prior to viral replication in the perinuclear area in the microtubule organizing center, where the new virions are assembled.…”
Section: Viral Spread To the Cnsmentioning
confidence: 99%
“…Interaction between the phosphoprotein of rabies virus, and LC8-the cytoplasmic dynein light chain that regulates microtubule-mediated transport-is implicated in viral transport [69][70][71]. However, mutant viruses with deletion in phosphoprotein encompassing LC8-interacting motif retained their neuroivasiveness and virulence [72]. Neuroattenuation required simultaneous substitution of arginine at position 333 of viral glycoprotein with deletion of LC8, reinforcing that rabies viral glycoprotein plays a more important role than phosphoprotein [72].…”
Section: Viral Spread To the Cnsmentioning
confidence: 99%
“…O sítio II é descontínuo e está localizado nas posições 34-42 e 198-200 ligadas por pontes dissulfeto (TORDO, 1996). Além disso, a arginina na posição 333 da glicoproteína G tem sido descrita como responsável pela patogenicidade do RABV (TORDO, 1996;MEBATSION, 2001).…”
Section: Lista De Figurasunclassified